2013
DOI: 10.1111/ans.12074
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular therapy for penetrating ulcers of the infrarenal aorta

Abstract: Urgent and elective endovascular repair of aPAUs can be achieved with high technical success. The significant co-morbid status of the treated patients is illustrated in the considerable in-hospital mortality and underlines the advantage of such treatment over open surgical repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…741,583 PAU are symptomatic in 18e70% causing pain (52%) or acute lower limb ischaemia because of distal embolism (12%) or rupture (4.1e6.9%). 741,[743][744][745] Isolated abdominal aortic dissections (IAAD) are rare and much less common than abdominal aortic dissection associated with thoracic aortic dissection. 746 The dissection is related to a tear in the intimal layer and subsequent blood flow through the tear into the media creating a false lumen.…”
Section: Penetrating Aortic Ulcer Pseudoaneurysm Intramural Haematoma Local Dissection and Saccular Aneurysmmentioning
confidence: 99%
See 2 more Smart Citations
“…741,583 PAU are symptomatic in 18e70% causing pain (52%) or acute lower limb ischaemia because of distal embolism (12%) or rupture (4.1e6.9%). 741,[743][744][745] Isolated abdominal aortic dissections (IAAD) are rare and much less common than abdominal aortic dissection associated with thoracic aortic dissection. 746 The dissection is related to a tear in the intimal layer and subsequent blood flow through the tear into the media creating a false lumen.…”
Section: Penetrating Aortic Ulcer Pseudoaneurysm Intramural Haematoma Local Dissection and Saccular Aneurysmmentioning
confidence: 99%
“…Serial imaging surveillance by cross sectional imaging (CTA or MRA) is justified since the natural course is largely unknown 743 , 744 . The assessment of an ulcer includes the measurement of the maximum aortic diameter at the ulcer site, the depth of the ulcer, and the length of the intimal defect (width) at the ulcer site.…”
Section: Penetrating Aortic Ulcer Pseudoaneurysm Intramural Haematoma Local Dissection and Saccular Aneurysmmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature review revealed mainly case reports of PAUs at the level of the AA and a rare series of greater than 10 cases. We collected 298 published cases of PAUs of the AA (Table 1) [12,13,17,18,21–61].…”
Section: Discussionmentioning
confidence: 99%
“…Conservative management with close observation for symptoms and no urgent surgical intervention determined in this natural history study of asymptomatic PUIA stands in contrast to other case series that advocate surgical therapy. 3,4,6,10…”
Section: Discussionmentioning
confidence: 99%